(untitled) (Nigerian Journal of Technology, 2021)
Unmanned aerial vehicles (UAVs) are tools for mechanized agriculture: they are used to alleviate maladies in a variety of fields through commercial, scientific, agricultural, and infrastructure enhancement. The purpose of the paper is to illuminate knowledge on mechanized agriculture using unmanned aircraft systems for pesticides and fertilizer application in obstacle rich farm. Various journal papers were reviewed to ascertain the state-of-the-art in agricultural unmanned aerial vehicles. X-rayed are unmanned aerial vehicle agrochemicals spraying architecture and efficacy, deployment and control strategies, obstacle sensing and avoidance systems, development/studies, and the limitations of the technology. The review shows that great strides have been made to develop agricultural unmanned aerial vehicles that can autonomously identify obstacle type, realize desired avoidance actions, and carry out variable rate agrochemical application. It is however noted that studies should continue on developing protocols and standard operation procedure, more human friendly interface platform, power technology, higher payload, real time quality imagery and robust mechanical features as well as enhanced sense and avoidance technology to meet the requirement of agricultural unmanned aerial vehicle for real time autonomous actions, flight endurance, low speed and low altitude. The paper therefore addressed the lack of awareness and absence of dedicated education on precision agriculture in the farming sector that has since ensured that its adoption level as a preferred system of farming remains very low in Nigeria despite the many benefits of unmanned aircraft vehicle farming technology.